Integrating Legal, Ethical, and Technological Strategies to Mitigate AI Deepfake Risks through Strategic Communication. (International Journal of Scientific Research and Management (IJSRM), 2023)
This study explores the critical role of legal education in addressing the challenges posed by AI deepfakes, with a focus on integrating deepfake-related topics into the curriculum to better prepare legal professionals. The primary objective is to examine how legal education can be enhanced to equip future lawyers with the necessary skills to navigate the ethical, legal, and technological implications of AI deepfakes. The study employs a theoretical approach, analyzing existing literature, case studies, and current legal frameworks to identify gaps in legal education and propose strategies for integrating AI deepfake topics into both foundational and continuing legal education (CLE) programs. The findings suggest that incorporating AI deepfake education into legal training can significantly enhance legal professionals’ ability to address the complex challenges posed by this technology. Key strategies include developing specialized modules, implementing scenario-based learning, and fostering interdisciplinary collaboration. The study highlights the broader implications of these findings for future research and practice, emphasizing the need for ongoing updates to legal curricula and the importance of continuous professional development. The integration of AI deepfake education is not only necessary for legal practice but also for shaping ethical and legal standards in the digital age.